Boundary Work and the Complexity of Natural Resources Management - Mollinga, Peter P. (Wiley, 2010)
This paper discusses how research on natural resources management systems can address the complexity of such systems. Three different types of complexity are identified: ontological, societal, and analytical. Significant ideas for “dealing with complexity” are extracted from U.S., Swiss, and U.K. literature on inter‐ and transdisciplinary research. Based on this, the “boundary work” framework is presented to systematically think through complexity challenges. The framework suggests that inter‐ and transdisciplinary research on natural research management requires three types of work: (i) the development of suitable boundary concepts that allow thinking of the multidimensionality of NRM issues; (ii) the configuration of adequate boundary objects as devices and methods that allow acting in situations of incomplete knowledge, nonlinearity, and divergent interests; and (iii) the shaping of conducive boundary settings in which these concepts, devices, and methods can be fruitfully developed and effectively put to work. The ideas presented are illustrated with an example of a research program on sustainable land and water management in Uzbekistan. The concluding section highlights three issues important for increasing the effectiveness of inter‐ and transdisciplinary research on natural resources management.